Pentingnya Regulasi dalam Mendukung Transformasi Digital di Industri Keuangan (Fintech) - Maslahah Maslahah; Sulistiawati Sulistiawati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
With technological innovation in the financial sector (Fintech), the development of digital technology has brought great changes to the financial industry. However, behind these advantages, there are challenges that need to be overcome, one of which is data security and user privacy which is a major issue that must be faced by the financial industry. This study aims to see how regulations help the digital transformation of Indonesia's financial industry (fintech). This study is a qualitative research, in accordance with the object of study, this type of research falls into the category of library research.Regulation of the financial technology (fintech) sector is borne by many parties, including the government, non-governmental organisations, and industry players. In Indonesia, institutions such as the Otoritas Jasa Keuangan (OJK) and Bank Indonesia (BI) are responsible for shaping fintech policies and regulations.Regulations serve as a strong foundation to drive digital transformation in the financial industry. Flexible and inventive regulations protect consumers and encourage profitable investments for industry players. A clear legal framework allows financial institutions to innovate and produce financial goods and services that better suit the needs of society.